New insights on circumscribed choroidal hemangioma: “bench to bedside” - Lupidi, Marco; Centini, Chiara; Castellucci, Greta; Nicolai, Michele; Lassandro, Nicola; Cagini, Carlo; Rizzo, Clara; Chhablani, Jay; Mariotti, Cesare (Graefe's archive for clinical and experimental ophthalmology, 2024)
Circumscribed choroidal hemangioma is a rare vascular hamartoma of the choroid, presenting as a red–orange mass at the posterior pole on fundoscopic examination. Despite its benign origin, associated complications such as subretinal fluid, serous retinal detachment, retinoschisis and neovascular glaucoma may lead to serious visual impairment in more than half patients. Because of its similarity to amelanotic choroidal melanoma and choroidal metastasis, differential diagnosis is still challenging for specialists. Multimodal imaging such as ultrasonography, fluorescein angiography, indocyanine green angiography, optical coherence tomography, and optical coherence tomography angiography guides the clinician to the correct diagnosis and the proper follow-up. Treatment is indicated in symptomatic cases in order to resolve exudation and improve visual acuity. Treatment options include photocoagulation, transpupillary thermotherapy, radiation therapy, photodynamic therapy and anti-vascular endothelial growth factor therapy. Currently, photodynamic therapy is the treatment of choice due to its effectiveness and safety. The purpose of this review is to describe the latest knowledge in the etiopathogenesis of the circumscribed choroidal hemangioma, the most recent multimodal imaging findings, and the available treatment options.